Complete Assembly of Escherichia coli Sequence Type 131 Genomes Using Long Reads Demonstrates Antibiotic Resistance Gene Variation within Diverse Plasmid and Chromosomal Contexts - Arun Gonzales Decano (American Society for Microbiology, 2019)
ABSTRACT The incidence of infections caused by extraintestinal Escherichia coli (ExPEC) is rising globally, which is a major public health concern. ExPEC strains that are resistant to antimicrobials have been associated with excess mortality, prolonged hospital stays, and higher health care costs. E. coli sequence type 131 (ST131) is a major ExPEC clonal group worldwide, with variable plasmid composition, and has an array of genes enabling antimicrobial resistance (AMR). ST131 isolates frequently encode the AMR genes blaCTX-M-14, blaCTX-M-15, and blaCTX-M-27, which are often rearranged, amplified, and translocated by mobile genetic elements (MGEs). Short DNA reads do not fully resolve the architecture of repetitive elements on plasmids to allow MGE structures encoding blaCTX-M genes to be fully determined. Here, we performed long-read sequencing to decipher the genome structures of six E. coli ST131 isolates from six patients. Most long-read assemblies generated entire chromosomes and plasmids as single contigs, in contrast to more fragmented assemblies created with short reads alone. The long-read assemblies highlighted diverse accessory genomes with blaCTX-M-15, blaCTX-M-14, and blaCTX-M-27 genes identified in three, one, and one isolates, respectively. One sample had no blaCTX-M gene. Two samples had chromosomal blaCTX-M-14 and blaCTX-M-15 genes, and the latter was at three distinct locations, likely transposed by the adjacent MGEs: ISEcp1, IS903B, and Tn2. This study showed that AMR genes exist in multiple different chromosomal and plasmid contexts, even between closely related isolates within a clonal group such as E. coli ST131. IMPORTANCE Drug-resistant bacteria are a major cause of illness worldwide, and a specific subtype called Escherichia coli ST131 causes a significant number of these infections. ST131 bacteria become resistant to treatments by modifying their DNA and by transferring genes among one another via large packages of genes called plasmids, like a game of pass-the-parcel. Tackling infections more effectively requires a better understanding of what plasmids are being exchanged and their exact contents. To achieve this, we applied new high-resolution DNA sequencing technology to six ST131 samples from infected patients and compared the output to that of an existing approach. A combination of methods shows that drug resistance genes on plasmids are highly mobile because they can jump into ST131’s chromosomes. We found that the plasmids are very elastic and undergo extensive rearrangements even in closely related samples. This application of DNA sequencing technologies illustrates at a new level the highly dynamic nature of ST131 genomes.